Síntese Verde de compostos quinolínicos e sua importância na química medicinal - Alponti, Leonardo Henrique Rondini (Universidade Federal de São Carlos, 2022)
Medicinal chemistry and synthetic organic chemistry have established themselves as great allies of human development, producing bioactive compounds intended at the development of pharmaceuticals, agrochemicals and veterinary products. The N-heterocyclic compounds, which are present in the central skeleton of several natural products, have been widely studied, especially for obtaining drugs, since they are able to modify, modulate and optimize the properties according to the need in therapeutic treatments. Among this class, those that have the quinolinic nucleus in their structure deserve to be highlighted because of their wide range of pharmacological activities. In the literature there are classic routes for the synthesis of quinoline derivatives, however, even if efficient, many of them require conditions that affect the safety of the environment and the operator. Thus, it is necessary to study and expand different methods and techniques that follow the green chemistry principles and provide synthetic protocols that are as sustainable as possible, and effective at the same time. In this work, in addition to a review about the history, structure, synthesis and various applications of quinolinic compounds, methodologies developed in recent years that include their formation through C-H functionalization reactions were also be explored. More specifically, the formation of new derivatives from quinoline N-oxide and 1,3-oxazoline-2-thione were evaluated. Two quinolinic compounds denominated 3a (yield: 7-29%) and 3b (yield: 10-28%) were obtained, and the perspective is to continue optimizing the reaction, in order to explore its derivatives and introduce the study of bioactivity and possible applications.
Green Synthesis of quinolinic compounds and their importance on medicinal chemistry
Keywords: Síntese verde; Funcionalização C-H; Quinolina; Heterociclos nitrogenados; Química medicinal; Compostos bioativos; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::SINTESE ORGANICA